Effect of Quercus infectoria G. Olivier Extracts On Antibiotic-resistant Staphylococcus aureus - Sasitorn Chusri (Prince of Songkla University, 2016)
Thesis (Ph.D.,Microbiology)--Prince of Songkla University, 2010